Illegal Migration from Mexico to the United States - Hanson, Gordon H (Journal of Economic Literature, 2006)
In this paper, I selectively review recent literature on illegal migration from Mexico to the United States. I begin by discussing methods for estimating stocks and flows of illegal migrants. While there is uncertainty about the size of the unauthorized population, new data sources make it possible to examine the composition of legal and illegal populations and the time-series covariates of illegal labor flows. I then consider the supply of and demand for illegal migrants. Wage differentials between the United States and Mexico are hardly a new phenomenon, yet illegal migration from Mexico did not reach high levels until recently. An increase in the relative size of Mexico's working-age population, greater volatility in U.S.–Mexico relative wages, and changes in U.S. immigration policies are all candidate explanations for increasing labor flows from Mexico. Finally, I consider policies that regulate the cross-border flow of illegal migrants. While U.S. laws mandate that authorities prevent illegal entry and punish firms that hire unauthorized immigrants, these laws are imperfectly enforced. Lax enforcement may reflect political pressure by employers and other interests that favor open borders.